The Effect of Leadership and Motivation on Productivity Employees at PT. ISS Indonesia Bintaro - South Tangerang - Ahmad Nazir; Achmad Nur Sholeh; Akhmar Barsah; Mochamad Aceng (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to determine the effect of leadership and motivation on employee productivity at PT. ISS Indonesia Bintaro, South Tangerang, either partially or simultaneously. The method used in this research is descriptive quantitative by using saturated sampling technique that is as many as 161 employees are all used as respondents. The results of leadership research have a significant effect on employee productivity with the regression equation Y= 18,667 + 0,218X1, the correlation coefficient value is 0,970 (low), the termination coefficient is 10.9%. hypothesis test obtained count > t table or (2657, > 1,975). Thus H0 is rejected and H1 is accepted, meaning that there is a partially significant influence between leadership on employee productivity. Motivation has a significant effect on employee productivity with the regression equation Y = 18.677 + 0.187X2, the correlation coefficient value is 0.263 (low), the coefficient of determination is 11.7%. Hypothesis test obtained t count > t table or (1,923 < 1,975). Thus H0 is accepted and H2 is rejected, meaning that there is no partial significant effect between motivation on employee productivity. Leadership and motivation have a positive effect on employee productivity with the regression equation Y = 18.677 + 0.218X1 + 0.187X2, the correlation coefficient value is 0.156, meaning that the independent variable and the dependent variable have a low level of relationship, the coefficient of determination is 15.6%, hypothesis testing obtained the calculated F value > Ftable or (9.670 > 3.04). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between leadership and motivation on employee productivity at PT. ISS Indonesia Bintaro – South Tangerang.